Inclusion Complexes of Ethanamizuril with β- and Hydroxypropyl-β-Cyclodextrin in Aqueous Solution and in Solid State: A Comparison Study - Guo, Juan; Zhang, Lifang; Wang, Mi; Liu, Yingchun; Fei, Chenzhong (Molecules (Basel, Switzerland), 2024)
Ethanamizuril (EZL) is a new anticoccidial drug developed by our Shanghai Veterinary Research Institute. Since EZL is almost insoluble in water, we conducted a study to improve the solubility of EZL by forming inclusion complexes with β-cyclodextrin (β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD). In this study, we performed molecular docking and then systematically compared the interactions of EZL with β-CD and HP-β-CD in both aqueous solution and the solid state, aiming to elucidate the solubilization effect and mechanism of cyclodextrins (CDs). The interactions were also examined in the solid state using DSC, PXRD, and FT-IR. The interactions of EZL with CDs in an aqueous solution were investigated using PSA, UV-vis spectroscopy, MS, 1H NMR, and 2D ROESY. The results of phase solubility experiments revealed that both β-CD and HP-β-CD formed inclusion complexes with EZL in a 1:1 molar ratio. Among them, HP-β-CD exhibited higher Kf (stability constant) and CE (complexation efficiency) values as well as a stronger solubilization effect. Furthermore, the two cyclodextrins were found to interact with EZL in a similar manner. The results of our FT-IR and 2D ROESY experiments are in agreement with the theoretical results derived from molecular simulations. These results indicated that intermolecular hydrogen bonds existing between the C=O group on the triazine ring of EZL and the O-H group of CDs, as well as the hydrophobic interactions between the hydrogen on the benzene ring of EZL and the hydrogen of CDs, played crucial roles in the formation of EZL/CD inclusion complexes. The results of this study can lay the foundation for the future development of high-concentration drinking water delivery formulations for EZL.